Finite element modeling, correlation and model updating of stiffened plate - Abd. Rahman, Roslan; Zubair, Mazlan; Amin, Norsham (Faculty of Mechanical Engineering, 2003)
This paper looks into modal parameter extraction of aluminium plate using finite element (FE) analysis and the correlation with experimental modal analysis. The effects of localize stiffening with ribs on modal parameters were considered. Finite element models of an aluminium plate with and without rib were developed and analyzed. Correlation and model updating of the stiffening plate were considered. Results suggest that ribs increase the local stiffness of the plate and they can be added onto a structure during modification.